Prospects for the development of digital audit in the Republic of Kazakhstan in the context of the transition to the digital economy. - V. I. Berezuk (Учёт. Анализ. Аудит, 2024)
The article discusses the development of digital audit in the Republic of Kazakhstan, the implementation of which is designed to ensure the transparency of business processes that are most susceptible to corruption. The purpose of the research is to study promising directions for the development of digitalization in auditing activities. The author has established the fact that the economic security of the country and its further development depend on this. The solution to the problems posed in the work was carried out on the basis of the application of general scientific research methods within the framework of comparative, logical and statistical analysis of structure and dynamics, graphic interpretation of information, etc. The practical significance of the study is confirmed by the definition of a set of practical recommendations for improving digital audit. The work provides data that can complement existing approaches to conducting digital audits and identify its role at the present stage. Data obtained in the process of studying scientific literature and regulatory and legal sources indicate that in modern conditions there are problems that acutely affect the process of digitalization of the economy of Kazakhstan and require immediate solutions. Among them is the improvement of the country’s economic policy in the field of development of the audit services market. The recommendations proposed by the author of the article are intended to help in resolving issues related to conducting a digital audit, as well as identifying new approaches to theoretical and applied research in the field of digitalization of business processes and can be useful to specialists in accounting and auditing, students, masters, doctoral students.